Quality control of involved field radiotherapy in the HD 13 and HD 14 trials: report of the radiotherapy panel of the German Hodgkin Study Group (GHSG) - Kriz, Jan; Herfarth, Klaus (Strahlentherapie und Onkologie, 2017)
Abstract: Introduction: As part of the foundation of the German Hodgkin Study Group (GHSG) in 1978, a central radiotherapy (RT) reference centre was established to evaluate and to improve the quality of treatment. During the study generations, the quality assurance programs (QAP) were continued and adapted to the demands of each study. The purpose of this article is to demonstrate the results of the fifth study generation and to compare them to the previous findings. Methods: With the start of the fourth GHSG study generation (HD10–12), a central prospective review of all diagnostic images was established to create an individual treatment plan for each early stage study patient. The quality of involved field RT was retrospectively evaluated by an expert panel of radiation oncologists. In the fifth study generation (HD13–15), the retrospective review of radiotherapy performed was refined and the results were compared with the findings of the fourth generation. Results: The expert panel analyzed the RT planning and application of 1037 (28 %) patients (HD13 n = 465, HD14 n = 572). Simulation films were available in 85 % of cases and verification films in 87 %. RT was assessed as major violation in 46 % (HD13 = 38 %, HD14 = 52 %), minor violation in 9 % (HD13 = 9 %, HD14 = 9 %) and according to the protocol in 45 % (HD13 = 52 %, HD14 = 38 %). Conclusion: The value for QAP of RT within the GHSG trials is well known. Still there were several protocol violations. In the future, the QAP program has to be adapted to the requirements of “modern RT” in malignant lymphoma.
First published: 5 September 2016
Autorenname Herfarth im Artikel als Herfart genannt
Gesehen am 28.06.2018